Social Media Marketing & E-WOM: Efforts To Increase Repurchase Intention Through Strong Brand Trust - Fathorrahman, Fathorrahman; Widodo, Teguh; Yanto, Vincent (UNIVED Press, 2026)
The rapid development of technology has led to the increasing growth of the internet. This rapid internet growth has impacted the advancement of online commerce. In today's era of globalization, online shopping services are the most effective way for people to shop. Generation Z is a generation that largely uses digital platforms like Shopee. Based on initial observations conducted by the researcher, the study indicates a high level of consumption and repurchase behavior among Generation Z through the e-commerce application Shopee. Repurchase intention can be considered one of the important factors in consumer purchasing, as consumers make a second purchase, and so on, having already developed both emotional and functional attachment. The research population is Generation Z in Malang City who have purchased products on Shopee, with a sample of 150 respondents. The sampling technique used is simple random sampling. Data collection was carried out by distributing questionnaires directly and through Google Forms to selected respondents who had made purchases on Shopee. Data analysis was performed using the SmartPLS analysis tool.The results of this study conclude that first, Shopee consumer repurchase intention in Malang City is directly influenced by Social media marketing and brand trust, but not by the E-WOM variable. Second, the brand trust variable is directly influenced by Social media marketing and E-WOM. Third, the brand trust variable partially mediates the influence of Social media marketing on repurchase intention, but fully mediates the influence of E-WOM on repurchase intention of Shopee consumers in Malang City.